Oscillation Phenomenon in Trust-Region-Based Sequential Convex Programming for the Nonlinear Trajectory Planning Problem - Xie, Lei; He, Rui-Zhi; Zhang, Hong-Bo; Tang, Guo-Jian (IEEE transactions on aerospace and electronic systems, 2022)
The trust-region-based sequential convex programming (TSCP) method is designed to solve the nonlinear trajectory planning problem using successive linearization and trust region. The TSCP method has a good real-time performance suitable for onboard aerospace applications. However, the main challenge in practical applications is its poor convergence. In this article, we reveal an oscillation phenomenon, which is an important factor affecting the convergence. The main contribution of this article is threefold: 1) the oscillation phenomenon is proved to be an inherent property of the TSCP method for the nonlinear trajectory planning problem; 2) the oscillation condition that determines whether oscillation occurs is obtained; and 3) the oscillation-condition-based remedy to address the oscillation is presented. The effectiveness and robustness of the proposed remedy have been verified via a complex reentry trajectory planning problem.